The value of brands to shareholders - Haigh, David (Henry Stewart Talks, 2010)
Who are the stakeholders, How to maximize shareholder value through intangible assets, Understanding International Financial Reporting Standard 3, What are brands and how do you value them?, Strategies for engaging with the Chief Financial Officer, Case Study: Orange